(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article examines effective mechanisms for monitoring professional competencies of students in vocational education institutions. It analyzes the importance of competency-based assessment and highlights approaches such as criteria-based evaluation, portfolio assessment, digital monitoring platforms, and performance-based assessment in real and simulated workplaces. The study emphasizes the role of continuous, formative, and summative monitoring in ensuring transparency, fairness, and alignment with labor market needs. It concludes that integrating digital technologies, workplace feedback, and data-driven decision-making into the monitoring process can significantly improve the quality of vocational training and support the development of employable, innovative, and responsible graduates.